O direito ao esquecimento na era digital: desafios da regulação da desvinculação de urls prejudiciais a pessoas naturais nos índices de pesquisa dos buscadores horizontais - Gonçalves, Luciana Helena (2016)
In the 'Recurso Especial' regarding to the petition filed with the court by the broadcasting presenter, Xuxa Meneghel, in order to compel Google Search to delist the results related to the expression 'Xuxa pedophile' or to any other term which would link her name to this criminal act from its search engine index, the Reporting Judge of this decision, Nancy Andrighi, has defined accurately the controversy of this dissertation: the daily life of thousands of people depends nowadays on the information which is on the web, and that would be not easily found without the use of the database provided by search engines. On the other hand, these search engines can be used to locate web pages with information, URLs which are results of the search under people’s names. In this way, what can be done? A right to be forgotten, in other words, the possibility of requiring the delisting of an URL from the search engine’s index which is a result of a search using the name of a person could really exist? There are people who affirm that the most appropriate measure to deal with this problem would be to reach out to the person who uploaded the content on the web. There are also people who defend that a right to be forgotten protection would represent a big threat to the freedom of expression. Before this context, this dissertation aims at establishing which could be the characteristics and limits of the right to be forgotten in the digital era, by taking into account the current condition of the Brazilian legal system in respect of this topic. In this way, this right will be confronted with other rights and public and private interests (specially the right to freedom of expression and the right to information) and also consider the characteristics of the operation of the global computer network. By remembering of the importance of the electronic search engines in the exercise of the access to information and, moreover, the difficulties which are related to the delisting of the information from all the sites in which it had been published, our dissertation will focus on the potential – and on the difficulties – of using the regulation of these mechanisms of search for the effective protection of the right to be forgotten in the digital era.